Resistance mechanisms of white jabon seedlings (Anthocephalus cadamba) against Botryodiplodia theobromae causing dieback disease - LOLA ADRES YANTI; ACHMAD ACHMAD; NURUL KHUMAIDA (Biodiversitas Journal of Biological Diversity, 2018)
Yanti LA, Achmad, Khumaida N. 2018. Resistance mechanisms of white jabon seedlings (Anthocephalus cadamba) against Botryodiplodia theobromae causing dieback disease. Biodiversitas 19: 1441-1450. Anthocephalus cadamba (Roxb.) Miq. seedlings are the most preferred plant for the nursery as they serve a lot of benefits and can be used as shading trees, reforestation, plywood, pulp, paper, and traditional medicines. Further, those benefits can increase the economic value of this plant. The main problem in the nursery of forestry plants is pest and disease attacks, one of which is dieback disease. The dieback disease is caused by Botryodiplodia theobromae Pat. that may lead death of the host plant. Every plant has its resistance mechanism toward pathogen attacks. This research aimed: (1) to study B. theobromae attack through wounded and non-wounded stem infection methods on white jabon seedlings; (2) to study the resistance mechanisms of white jabon seedlings both structural and biochemical resistance against B. theobromae. This study employed a factorial treatment design laid out in a completely randomized design. The structural resistance was determined by studying the microscopic appearance of the white jabon seedlings’ stem by using a scanning electron microscope. Meanwhile, the biochemical resistance was determined by characterizing the chemical compounds of white jabon seedlings' stem using phytochemistry analysis. The result showed that the disease incidence of the control (inoculated without pathogen isolate) and the inoculated (inoculated with pathogen isolate) seedlings were, respectively, 0% and 100% (with wounded stem) and 0% and 30% (non-wounded). The disease severity of control and inoculated seedlings were 0% and 62% (with wounded stem) and 0% and 12% (non-wounded stem), respectively. The incubation period of wounded and non-wounded stems on inoculated seedlings (inoculated with pathogen isolate) was one day after inoculation with the numeric values (disease scores) of 4 and 2, respectively. White jabon seedlings had necrotic resistance as structural resistance mechanism against the pathogen attack. White jabon seedlings also contained secondary metabolites such as alkaloids, flavonoid, phenyl hydroquinone, tannin, saponin, and steroids. The biochemical resistance of white jabon seedling after pathogen attacks was shown by the increase of accumulated phenolic compounds such as flavonoid and tannin.